Insecticide resistance monitoring in field populations of Chilo suppressalis Walker (Lepidoptera: Crambidae) from central China - Meng, Haoran; Huang, Rong; Wan, Hu; Li, Jianhong; Li, Junkai; Zhang, Xiaolei (Frontiers in Physiology, 2022)
Chilo suppressalis walker (Lepidoptera: Crambidae) is an important pest on rice crop in China. And effective management of C. suppressalis field populations in most of the China’s agriculture regions is dependent on chemical insecticide. Currently, C. suppressalis has developed widespread resistance to many active ingredients due to intensive and extensive application of them. Thus, insecticide resistance development is an important concern for all crop specialists and growers. In the study, we determined the susceptibility of forty-six field populations of C. suppressalis to three insecticides by topical application method from 2010 to 2021 in three provinces of Central China. The studies showed that field populations of C. suppressalis have developed moderate to high levels of resistance to triazophos (Resistance Ratio, RR = 41.9−250.0), low to moderate levels of resistance to chlorpyrifos (RR = 9.5−95.2) except for Zhijiang population in 2013 with a 4.8-fold resistance and Xinyang population in 2015 with a 3.4-fold resistance, while they remained susceptible to moderate levels of resistance to abamectin (RR = 4.1−53.5). The results in the study will be beneficial for effective insecticide resistance management strategies to reduce the risk of rapid building-up of resistance to insecticide and slow down the process of selection for insecticide resistance.